Drivers and Barriers Influencing Sustainable Food Procurement in the Hospitality Industry - Reis, A.; Simaens, A. (5th Symposium on Ethics and Social Responsibility Research, 2019)
In late years, the tourism and hospitality industry became one of the most important contributors to the global economy and sustainable development. Regrettably, despite all of the potential benefits recognized to this sector have shown to drag along some not only environmental but also social and inevitably economic consequences (Bohdanowicz, 2005). Corporate responsibility is now accepted to be a viable strategy to achieve competitive advantages as well as stakeholders’ satisfaction. According to the Center for Responsible Travel (2016), sustainability has actually become popular amongst businesses in the tourism and hotel industry with many of them implementing environmentally friendly policies and strategies, applying for green certifications and going for sustainable supply chain management. Indeed, travellers have shown more interest in staying at environmentally friendly hotels (Manaktola & Jauhari, 2007). By interviewing representatives from six Lisbon hotels and one expert association, the present study aims to identify the drivers and barriers influencing a hotel’s ability to implement a sustainable food procurement system as well as to determine how, and in what ways, specific hotel characteristics and market position can impact its motivations, setbacks and overall ability to manage food procurement in a sustainable way. The interviews’ responses and the case-studies have shown how the quest for quality, internal and external communication, education and mutual collaboration with all stakeholders, corporate responsibility programs and guidelines and ultimately, business values and philosophy are the more recurrent reasons motivating hotels to achieve sustainable food procurement. On the other hand, the lack of prioritization of sustainable objectives, lack of implementation of such values throughout all hierarchies, lack of administrative freedom and an overall lack of sustainable supply chains and sustainable suppliers and products have been identified as the biggest difficulties hampering the process of implementing sustainable food procurement policies. Despite many factors being identified as possible factors affecting these results, we have ultimately concluded that a balance between sustainable development, customer satisfaction and financial sustainability are key for the achievement of sustainability-related policies.